Validation of the EKFC equation for glomerular filtration rate estimation and comparison with the Asian-modified CKD-EPI equation in Chinese chronic kidney disease patients in an external study - Li Zhao; Huan-li Li; Hui-jing Liu; Jin Ma; Wei Liu; Jian-min Huang; Ling-ge Wei; Peng Xie (Renal Failure)
Objectives The aim of this study is to determine whether new European Kidney Function Consortium (EKFC) equation is more applicable than Asian-modified CKD-EPI equation in clinical practice, having a higher accuracy in estimating GFR in our external CKD population.Methods We calculated estimated GFREKFC and GFRCKD-EPI independently using the EKFC and Asian-modified CKD-EPI formulas, respectively. The clinical diagnostic performance of the two equations was assessed and compared by median bias, precision, accuracy (P30) and so on, using 99mTc-DTPA dual plasma sample clearance method as a reference method for GFR measurement (mGFR). The equation that met the following targets was superior: (1) median bias within ± 3 mL/min/1.73 m2; (2) P30 > 75%; and (3) better precision and 95% limits of agreement in Bland–Altman analysis.Results Totally, 160 CKD patients were recruited in our external cohort. GFREKFC was highly related to mGFR, with a regression equation of GFREKFC=mGFR × 0.87 + 5.27. Compared with the Asian-modified CKD-EPI equation, EKFC equation demonstrated a wider median bias (–1.64 vs. 0.84 mL/min/1.73 m2, p < 0.01) that was within 3 mL/min/1.73 m2 and not clinically meaningful. Furthermore, the precision (12.69 vs. 12.72 mL/min/1.73 m2, p = 0.42), 95% limits of agreement in Bland–Altman analysis (42.4 vs. 44.4 mL/min/1.73 m2) and incorrect reclassification index of the two target equations were almost identical. Although, EKFC equation had a slightly better P30 (80.0% vs. 74.4%, p = 0.01).Conclusions The overall performance of EKFC equation is acceptable. There is no clinically meaningful difference in the performance of the Asian-modified CKD-EPI and EKFC equations within the limits imposed by the small sample size.